Investigating the Relationship Between General Anesthesia and Early Brain Atrophy: A Case-control Study - Zoubin Souri; Mahsa Eghrari Gigloo; Soheil Soltanipour; Hakimeh Sarshad; Gelareh Biazar (Caspian Journal of Neurological Sciences)
Background: Brain atrophy is a common finding in older people. However, in some cases, brain atrophy is not proportional to the patient’s age. Recently, there has been much focus on the neurotoxicity of anesthetic drugs. Objectives: This study was planned to investigate whether exposure to anesthesia accelerates the process of brain atrophy. Materials & Methods: This case-control study was conducted in two academic hospitals affiliated with Guilan University of Medical Sciences (GUMS), Rasht City, Iran, from May 2024 to August 2024. Patients with early brain atrophy were included as the case group, and those who did not have early brain atrophy as the control group; 27 people in each group were studied. A checklist containing demographic data, history of receiving anesthesia, age of receiving anesthesia, and number of times receiving anesthesia was completed and the obtained data were compared between the two groups. Results: Regarding demographic data, no significant difference was observed between the two groups (P>0.05). Although early brain atrophy was more common in older people (62.59±8 vs 58±10.5 years), the difference was not significant (P=0.069). Two groups were also compared in terms of diabetes (P=0.054), hypertension (P=0.248), stroke (P=0.34), alcohol consumption and addiction (P=0.552). Regarding the history of receiving general anesthesia as the main variable of the study, the difference between the two groups was not significant (P=0.78). Conclusion: The results of this study did not show a significant association between receiving general anesthesia and early brain atrophy. However, given the remarkable limitations of this study and the valid evidence, well-planned future studies are welcome.